2014
DOI: 10.1212/wnl.0000000000000130
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal metabolic network activity in REM sleep behavior disorder

Abstract: Objective: To determine whether the Parkinson disease-related covariance pattern (PDRP) expression is abnormally increased in idiopathic REM sleep behavior disorder (RBD) and whether increased baseline activity is associated with greater individual risk of subsequent phenoconversion.Methods: For this cohort study, we recruited 2 groups of RBD and control subjects. Cohort 1 comprised 10 subjects with RBD (63.5 6 9.4 years old) and 10 healthy volunteers (62.7 6 8.6 years old) who underwent resting-state metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
124
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(140 citation statements)
references
References 34 publications
13
124
2
1
Order By: Relevance
“…In line with 2 previous studies, RBD subjects significantly expressed the PDRP 12, 13. Although on average, PDRP z ‐scores were lower in RBD subjects compared with PD/DLB, more than half of the RBD subjects already had a PDRP z ‐score in the range of PD patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with 2 previous studies, RBD subjects significantly expressed the PDRP 12, 13. Although on average, PDRP z ‐scores were lower in RBD subjects compared with PD/DLB, more than half of the RBD subjects already had a PDRP z ‐score in the range of PD patients.…”
Section: Discussionsupporting
confidence: 90%
“…To date, 2 groups have reported that RBD subjects have higher PDRP subject scores compared with controls 12, 13. In a longitudinal study of 17 RBD subjects, baseline PDRP expression was associated with a high risk of developing PD or DLB within 5 years 12…”
mentioning
confidence: 99%
“…Two studies demonstrated that idiopathic RBD patients significantly express the PDRP (44,45). This finding was recently confirmed by our group (Meles et al, unpublished data, 2013(Meles et al, unpublished data, -2016.…”
Section: Predicting Pd Onset In Idiopathic Rbdsupporting
confidence: 74%
“…In contrast, 3 idiopathic RBD patients who developed MSA 2-4 y later did not express the PDRP at baseline. A logistic regression model based on PDRP expression and age at baseline could accurately predict phenoconversion to PD/DLB (44). These findings indicate that network expression has potential as a marker for phenoconversion and may have additional value in predicting which phenotype a patient with idiopathic RBD will develop.…”
Section: Predicting Pd Onset In Idiopathic Rbdmentioning
confidence: 77%
“…In addition to loss of normal DMN activity, the earliest stages of neurodegenerative illnesses are often associated with increasing expression of independent, abnormal disease-related metabolic networks (15,18,20,21). Using our approach, we directly compared the time course of the changes in normal and pathological network activity that occur in patients with these disorders.…”
Section: Discussionmentioning
confidence: 99%